The Study of Clean Water Demand in Palangka Raya City, Central Kalimantan - Ulfa Fitriati; Aulia Isramaulana; Achyat Yulianto Adi Saputro (Center for Journal Management and Publication, 2021)
Palangka Raya as the capital city of Central Kalimantan become the center lane economy leading to increase population growth and clean water demand. There are still areas experiencing water shortage problems because of the difficulty of distributing clean water.Â Objectives of this study were to determine the amount of water demand in 2016, 2020, 2025, 2030 and 2035 to fulfill the community requirements. Water quality and supply capacity at the intake system are also be the purposes of this study.In this study, the calculation of population projections using statistical methods in which to observe the rate of population growth of the past to estimate the number of people in the future. There are several methods that can be used to analyze the population growth in the future, specifically Arithmetic, Geometric, Linear Regression, Exponential, and Logarithmic. For water quality field survey was conducted to test parameters such as temperature, electrical conductivity, the amount of dissolved solids, pH, turbidity, salinity, and dissolved oxygen measurements. The method in this research was using Arithmetic method because the correlation can be said to be excellent compared to other methods. Results of this research were clean water demand discharge town of Palangka Raya with consecutive results as follows in 2016; 2020; 2025; 2030; 2035 amounted to 451.03 L/sec, 737.14 L/sec, 1,162.34 L/sec, 1,425.83 L/sec, 1,571.12 L/sec. In the aspect of water quality, source of raw water used PDAM Palangka Raya unqualified the standards in terms of pH value, so the use of water was not safe for the residents of Palangka Raya city.